Development of Interactive Flipbook Media with Science Technology Society Approach to Improve Learning Outcomes on Genetic Mutation Material - Yofi Parmita; Sarwo Danuji; Hanif Rafika Putri (Universitas Pendidikan Mandalika, 2025)
This study aims to determine the feasibility of interactive flipbook media as learning media, determine student responses to interactive flipbook media with the STM (Science Technology Society) approach and improve student learning outcomes in learning biology, especially on genetic mutation material. This research is using the Research and Development (R&D) method with the ADDIE model (Analyse, Design, Develop, Implement, and Evaluate). his research was conducted at Baitul Arqom High School, Jember City, involving 25 students of class XII as subjects. The research design used was one-group pretest-posttest using an instrument in the form of 20 multiple choice questions to assess the improvement of learning outcomes to determine the difference in learning outcomes before and after the use of media. The media feasibility assessment was conducted by three experts, consisting of two biology education lecturers and one biology teacher. Meanwhile, students' responses to the learning media were obtained through the distribution of questionnaires. Based on the results of the study, it shows that the feasibility by material expert validators is 80%, media experts are 82%, and practitioner experts are 81% with an average percentage of 81% very feasible. Student responses to interactive flipbook media with the Science Technology Society (STM) approach scored 87% responded positively with a good category. The trial results showed an increase in student learning outcomes with an average N-Gain of 0.76, which is classified in the high category, as well as a normal distribution of N-Gain data. Overall, it can be concluded that the development of interactive flipbook media based on the Science Technology Society (STM) approach received a good response as learning media and proved effective in improving student learning outcomes, so it is feasible to use in the learning process.